Acacetin inhibits neuronal cell death induced by 6-hydroxydopamine in cellular Parkinson's disease model - Kim, Sang Min; Park, Yong Joo; Shin, Myoung-Sook; Kim, Ha-Ryong; Kim, Min Jae; Lee, Sang Hun; Yun, Seung Pil; Kwon, Seung-Hwan (Pergamon Press Ltd., 2017)
Acacetin (5,7-dihydroxy-4'-methoxyflavone), a flavonoid compound isolated from Flos Chrysanthemi Indici, chrysanthemum, safflower, and Calamintha and Linaria species has been shown to have anti-cancer activity, indicating its potential clinical value in cancer treatment. In this study, we sought to study the potentials of acacetin in preventing human dopaminergic neuronal death via inhibition of 6-hydroxy-dopamine (6-OHDA)-induced neuronal cell death in the SH-SY5Y cells. Our results suggest that acacetin was effective in preventing 6-OHDA-induced neuronal cell death through regulation of mitochondrialmediated cascade apoptotic cell death. Pretreatment with acacetin significantly inhibited neurotoxicity and neuronal cell death through reactive oxygen species (ROS) production and mitochondrial membrane potential (MMP) dysfunction. Acacetin also markedly acted on key molecules in apoptotic cell death pathways and reduced phosphorylation of c-Jun N-terminal kinase (JNK), p38 mitogen-activated protein kinase (MAPK), phosphatidylinositol 3-kinases (PI3K)/Akt, and glycogen synthase kinase-3beta (GSK-3b). These results suggested that acacetin could inhibit 6-OHDA-induced neuronal cell death originating from ROS-mediated cascade apoptosis pathway. Thus, the results of our study suggest that acacetin is a potent therapeutic agent for PD progression. (C) 2017 Elsevier Ltd. All rights reserved.